Silicon Nitride Film by Inline PECVD for Black Silicon Solar Cells - Bangwu Liu; Sihua Zhong; Jinhu Liu; Yang Xia; Chaobo Li (International Journal of Photoenergy)
The passivation process is of significant importance to produce high-efficiency black silicon solar cell due to its unique microstructure. The black silicon has been produced by plasma immersion ion implantation (PIII) process. And the Silicon nitride films were deposited by inline plasma-enhanced chemical vapor deposition (PECVD) to be used as the passivation layer for black silicon solar cell. The microstructure and physical properties of silicon nitride films were characterized by scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FTIR), spectroscopic ellipsometry, and the microwave photoconductance decay (μ-PCD) method. With optimizing the PECVD parameters, the conversion efficiency of black silicon solar cell can reach as high as 16.25%.